Hakikat Ego Manusia Perspektif Teori Filsafat Khudi Muhammad Iqbal - Mia Amelia; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This article explain about of Essense of human ego in Muhammad Iqbal’s khudi philosophy theory. The method used in this research is a qualitative method with data collection and specific literature through scientific articles and journals on the internet. In theoritic, this research explain about Iqbal’s philosphy perspective about human ego. In practice, this research give philophy’s view about human ego and it’s essense to known about his life existence. In this research can found that human ego is comes from God essense, but ego still has a free wil and not slaved from it essense. Based on the research result, it may be concluded that the ego is a human will that is free and governing as well as creative, which is created and comes from God as the Absolute ego, but is still based on the human will that gives rise to this will upon himself, and ego existence is important for human too because humans can become their unique selves as well as move towards to their essence, thai is God as the place to return from everything.